2022
DOI: 10.3390/vaccines10071062
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Seroreactivity Impacts the Accuracy of HIV Testing Algorithms in Sub-Saharan Africa: An Exploratory Study

Abstract: The detection of vaccine-induced HIV antibody responses by rapid diagnostic tests (RDTs) may confound the interpretation of HIV testing results. We assessed the impact of vaccine-induced seroreactivity (VISR) on the diagnosis of HIV in sub-Saharan Africa. Samples collected from healthy participants of HIVIS and TaMoVac HIV vaccine trials after the final vaccination were analyzed for VISR using HIV testing algorithms used in Mozambique and Tanzania that employ two sequential RDTs. The samples were also tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To improve the accuracy of HIV diagnostic algorithms, two to three RDTs are used in series or in parallel as screening, confirmatory, or tiebreaker tests. Considering the emotional trauma and social harms caused by HIV misdiagnosis, it is imperative that the RDT-based diagnostic strategies are able to discriminate HIV antibodies elicited by vaccination from those generated in response to an infection [34].…”
Section: How Did the Progress Made In Hiv Research Lay A Foundation F...mentioning
confidence: 99%
“…To improve the accuracy of HIV diagnostic algorithms, two to three RDTs are used in series or in parallel as screening, confirmatory, or tiebreaker tests. Considering the emotional trauma and social harms caused by HIV misdiagnosis, it is imperative that the RDT-based diagnostic strategies are able to discriminate HIV antibodies elicited by vaccination from those generated in response to an infection [34].…”
Section: How Did the Progress Made In Hiv Research Lay A Foundation F...mentioning
confidence: 99%
“…The results revealed that the Tanzanian diagnostic algorithm would have misdiagnosed as HIV-1 infected 54%, and the Mozambican—26% of the vaccinated healthy volunteers. However, the number of misdiagnoses decreased over time, and three years after vaccination, none of the 20 serum samples collected at that time tested HIV-1 positive using rapid diagnostic tests [ 59 ]. The reported results suggested that the HIV diagnostic algorithms used in these countries would have misclassified the healthy vaccine recipients as HIV-positive.…”
Section: Session 5: Facing New and Re-emerging Threatsmentioning
confidence: 99%